MANDAR MARTIAL ARTS TRADITIONS:AS A CHARACTER TO DEVELOP TOURISM ON TIDUNG ISLAND KEPULAUAN SERIBU DKI JAKARTA - Siti Gomo Attas; Gres Grasia Azmin; Marwiah Marwiah; Sarmadan Sarmadan (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
The Silat Mandar tradition can shape the character of the people of Tidung Island in order to develop tourism on Tidung Island. Silat Mandar is able to give color to people's lives in the DKI Jakarta area, especially Tidung Island in Kepualauan Seribu. Starting from the mythology of Bugis Mandar as an accomplished sailor, making the Bugis Mandar people a society that is undaunted to sail the ocean, such as the Bugis proverb "Once the sails are developed, it never recedes backwards".  It is the existence of this philosophy that memfor the Bugis if they have stuck their anchor at satu point they will try their best to survive and advance the region for an advancement. Likewise with the Bugis Mandar people on Tidung Island, this community grew out of a strong character from the influence of the Bugis Mandar culture which helped create a new culture on The Kepulauan Seribu. The Tradition of Silat Mandar as a tradition instilled by the Bugis Mandar people in this island. The theory used in this study is the theory of oral tradition and comodification, through observation techniques and interviews on the people of Tidung Island. The result of this study is how the Silat Mandar tradition which is used as a tradition that is developed and its character is instilled for the younger generation of the people of Tidung Island.  This tradition  has been contested and used as a lure for local and foreign tourists who visit Tidung Island.  The goal is to improve the welfare of its people, as well as revenue generating for the Regional Government and the Kepulauan Seribu Government.